2007
DOI: 10.1007/s00426-006-0106-y
|View full text |Cite
|
Sign up to set email alerts
|

Attentional demand and memory retrieval in negative priming

Abstract: Negative priming refers to delayed response to previous distractors, and can reflect the operation of attentional selection in prime trials. One important feature of negative priming is that it is modulated by the characteristics of probe trials. The current study manipulated competition from probe distractors and prime-probe similarity to examine the effects of attentional demand and memory retrieval in probe trials. The results demonstrated that the effects of attentional demand and memory retrieval on negat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
12
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 57 publications
1
12
0
Order By: Relevance
“…However, some of these studies (Fox & de Fockert, 1998;Stolz & Neely, 2001;Tse, Hutchison, & Li, 2011) confounded prime-probe contextual similarity with exact stimulus repetition (for details, see Tse et al, 2011). Studies without the confound showed that the negative priming effect increased when the prime and probe context were the same relative to a situation in which both contexts differed (Chao, 2009;Chao & Yeh, 2008;Neill, 1997; but see Wong, 2000). The modulatory effect of context repetition has been shown to be sensitive to temporal presentation parameters (see Experiment 1 by Neill, 1997, compared with Experiment 2 by Moore, 1996), spatial configurations (Chao & Yeh, 2008), and the variability of contextual cues (Chao, 2009).…”
Section: The Role Of Context In Negative Primingmentioning
confidence: 99%
“…However, some of these studies (Fox & de Fockert, 1998;Stolz & Neely, 2001;Tse, Hutchison, & Li, 2011) confounded prime-probe contextual similarity with exact stimulus repetition (for details, see Tse et al, 2011). Studies without the confound showed that the negative priming effect increased when the prime and probe context were the same relative to a situation in which both contexts differed (Chao, 2009;Chao & Yeh, 2008;Neill, 1997; but see Wong, 2000). The modulatory effect of context repetition has been shown to be sensitive to temporal presentation parameters (see Experiment 1 by Neill, 1997, compared with Experiment 2 by Moore, 1996), spatial configurations (Chao & Yeh, 2008), and the variability of contextual cues (Chao, 2009).…”
Section: The Role Of Context In Negative Primingmentioning
confidence: 99%
“…For the visual (Neill, Valdes, Terry, & Gorfein, 1992) as well as the auditory modality (Mayr & Buchner, 2006), temporal discriminability of the prime episode at the time of the probe presentation increases the negative priming effect. With respect to primeÁprobe contextual similarity, a majority of studies has demonstrated that the visual negative priming effect turns out to be larger when prime and probe presentations have a similar context (with respect to variables such as synchronicity of targetÁdistractor onsets or stimulusÁbackground contrast intensity) than when they differ in contextual variables (Chao & Yeh, 2008;Fox & de Fockert, 1998;Neill, 1997;Stolz & Neely, 2001; but see also Wong, 2000).…”
mentioning
confidence: 96%
“…Its valence can partly be determined by its previous association with an emotional context. Many affective priming studies examining memory processes, not always accompanied by brain imaging procedures, have reported behavioral effects predominantly after priming with negative stimuli (Stolz & Neely, 2001;Zhang et al, 2006;Chao et al, 2008). Intriguingly, to our knowledge, no brain imaging studies have so far examined the influence of emotional priming 5 on experiencing art.…”
mentioning
confidence: 99%